The effect of alcohol consumption on the risk of severe respiratory diseases : a series of systematic reviews and meta-analyses - Simou, Evangelia (2019)
Introduction: Alcohol is the most commonly used substance in the world and causes approximately 3.3 million deaths every year. Alcohol consumption is a well-recognized risk factor for a range of diseases and injuries. However, there is little knowledge on the relation between alcohol consumption and the occurrence of respiratory diseases.